PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Sakinah "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of corporate social responsibility (CSR) and capital structure on the value of the company in Mining companies in Indonesia Stock Exchange. Ratio of Corporate social responsibility (CSR) as independent variable using Corporate disclosure corporate social responsibility disclosure index. The ratio of capital structure used as independent variable is debt to equity ratio (DER) and debt to asset ratio (DAR). While the value of the company as a dependent variable is measured by the ratio of price book value (PBV) and price earnings ratio (PER). The method used to observe the effect of corporate social responsibility and capital structure on company value is by using multiple linear regression.The data used in this research are secondary data, financial report and annual report annual report. The data are listed on the Indonesia Stock Exchange (IDX) for 3 years from 2012 to 2014. Sampling is done by purposive sampling, which is used is 16 companies from 42 mining companies in Indonesia Stock Exchange. Data analysis using simple linear regression analysis, multiple linear regression analysis, t test, f test and coefficient of determination test. Data analysis using multiple linear regression analysis using SPSS 21.The result of the analysis shows that corporate social responsibility variable has no significant effect on corporate social responsibility towards the value of mining companies in Indonesia Stock Exchange. While the variable of capital structure does not affect the value of mining companies in Indonesia Stock Exchange. Results of simultaneous testing no significant influence of corporate social responsibility and capital structure variable to the value of mining companies in Indonesia Stock Exchange.Keywords: Corporate Social Responsibility, capital structure, corporate value